(untitled) (Jagannath University Journal of Science, 2024)
The goal is to scrutinize the thermal features of hybrid nanofluid in a square cavity with the effect of oblique periodic magnetic field. The modified hybrid nanofluid is a combination of nanoparticles , and base fluid water with equal volume fraction of and The finite element method based Galerkin weighted residual scheme is chosen to find the solution of the non-dimensional governing equations. The effects of different model factors such as oblique angle and period of the periodic magnetic field, Hartmann number, Rayleigh number, nanoparticles volume fraction on the heat transfer are scrutinized. The outcomes are exhibited with the help of isotherms and average Nusselt number as well. The numerical results show that when the period of the slanted periodic magnetic field increases gradually, the distinct model factors (Rayleigh number, nanoparticles volume fraction, and slanting angle) raise the heat transfer rate progressively, whereas augmentation of the Hartmann number diminutions the entire heat transfer rate. Jagannath University Journal of Science, Volume 10, Number II, Dec. 2023, pp. 75-86